Propuesta de un Balanced Scorecard para la empresa industria metálica cotopaxi, ubicada en la ciudad de Latacunga, parroquia san Buenaventura, en el periodo 2013 - Guanoluisa Guamushig, Miryan Pilar (2015)
This research was carried in order to get information on the problems within the strategic processes at Cotopaxi Metal Industry. It is located in Latacunga City. This proposal through of a Balanced Scorecard could obtain relevant and accurate management tool. The purpose is to operationalize objectives and strategies to achieve the company´s vision as an object of study. To measure the current status of internal and external factors, an organizational performance and level of fulfillment of their goals was determined. In addition, the identified needs were applied to the exploratory design as a research method….